Courage in Competition: Adaptation of the Sports Courage Scale for American English and Validation of the Factor Structure with Student-Athletes at Clemson University - Konter, Erkut; Kueh, Yee Cheng; Kuan, Garry (International journal of environmental research and public health, 2020)
While courage is widely attributed to athletic pursuits, it has received little scientific attention from both researchers and applied practitioners. A reliable measurement is required to examine courage in sports and competitive activities. Therefore, this research aimed to adapt the original Turkish Sports Courage Scale-31 into American English (SCS-AE). The SCS-31 measure was translated from Turkish into the American English language by the Brislin forward and backward translation technique and language validity. Then, the translated SCS-AE was administered to 548 American university college students (Mean age = 19.02, SD = 1.21). All participants played a sport (e.g., football, soccer, basketball, gymnastics). Based on confirmatory factor analyses (CFA), 31 items of SCS-AE were reduced to 24 items with four factors (i.e., assertiveness, determination, mastery, and venturesome). The fit indices were satisfactory (RMSEA = 0.06, CFI = 0.97, SRMR = 0.06, NFI = 0.96 and NNFI = 0.97). The internal consistency measured by Cronbach alpha, ranging from 0.73 to 0.78, were considered acceptable. The convergent validity and discriminant validity of SCS-AE were also achieved. Our findings indicate strong support for research using the four-factor model of the SCS-AE and adequate support for the five-factor model with sufficient caution regarding the internal consistency of the self-sacrifice factor. While cultural differences in courage perception might exist between these countries, the findings showed more similarities than differences in courage. Results indicated that the SCS-AE is usable for research purposes in the suggested format. Future directions are discussed using the SCS-31 and SCS-AE for research.